Metal (II) Complexes with Tridentate N, N,O Ligand: Synthesis, Characterization and Biological StudiesÂ - Niseaf, Ali N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The preparation of some new coordination compounds for nikel (II), manganese (II), copper (II), cobalt (II)and mercury (II), with ligand obtained from Benzoinand2-amino pyridine.The ligand[6-(2-hydroxy-1,2-diphenylethylideneamino)pyridin-3-ylium)](L) was made from reactin ethanol with metal salts in (1:1)(metal : ligand)ratio.[MLCl] was the inclusive formula of the complexes where M= Mn(II),Co(II),Ni(II),Cu(II) and Hg(II). Metal analysis by electronic spectra, atomic absorption ,infrared spectra, 1H&13C-NMR(only ligand)spectral studies, magnetic moment and molar conductance measurements used to describe the compounds.The determinations indicated that the ligand coordinates with the metal (II) ion in neutral tridentate manner through the azomethine nitrogen atom, nitrogen atom for pyridine and oxygen atom of the benzoin, all the studies reveal coordination four for the metals in all the complexes. Tetrahedral and square planar structures were suggested for metal complexes.